2022
DOI: 10.1017/jfm.2021.1134
|View full text |Cite
|
Sign up to set email alerts
|

Strong alignment of prolate ellipsoids in Taylor–Couette flow

Abstract: We report on the mobility and orientation of finite-size, neutrally buoyant, prolate ellipsoids (of aspect ratio $\varLambda =4$ ) in Taylor–Couette flow, using interface-resolved numerical simulations. The set-up consists of a particle-laden flow between a rotating inner and a stationary outer cylinder. The flow regimes explored are the well-known Taylor vortex, wavy vortex and turbulent Taylor vortex flow regimes. We simulate two particle sizes $\ell /d=0.1$ … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 54 publications
(81 reference statements)
0
13
0
Order By: Relevance
“…For high We = 400 (figure 3a-e), the secondary phase is highly fragmented, preferentially remains in the bulk region, and adopts unique repeating flow patterns in the axial (z) direction. The clustering trend of the dispersed phase in the bulk region is also observed for rigid particle suspensions for the Taylor vortex regime (Majji & Morris 2018; Assen et al 2022), which is caused by the linear shear gradient driving the suspended object towards the centre of the channel (Majji & Morris 2018). In our case, although the droplets are deformable and a free-slip boundary condition is imposed on the surface (instead of a no-slip condition, which is enforced on the particles), a similar mechanism might induce the migration of the droplets.…”
Section: Flow Visualisationsmentioning
confidence: 75%
See 4 more Smart Citations
“…For high We = 400 (figure 3a-e), the secondary phase is highly fragmented, preferentially remains in the bulk region, and adopts unique repeating flow patterns in the axial (z) direction. The clustering trend of the dispersed phase in the bulk region is also observed for rigid particle suspensions for the Taylor vortex regime (Majji & Morris 2018; Assen et al 2022), which is caused by the linear shear gradient driving the suspended object towards the centre of the channel (Majji & Morris 2018). In our case, although the droplets are deformable and a free-slip boundary condition is imposed on the surface (instead of a no-slip condition, which is enforced on the particles), a similar mechanism might induce the migration of the droplets.…”
Section: Flow Visualisationsmentioning
confidence: 75%
“…They revealed that the equilibrium positions were changed drastically for different flow regimes, starting from the centre of the channel (circular Couette flow regime), followed by circular regions in the r-z plane (Taylor vortex flow regime), and eventually distributing uniformly (wavy vortex flow regime). Assen et al (2022) analysed numerically the motions of finite-sized elliptic objects in Taylor-Couette flows from the Taylor vortex flow regime to the turbulent regime. They observed that the behaviour of particles (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations